Separation of metallic and semiconducting single walled carbon nanotubes using aqueous two-phase technique / Malcolm Tang Siong Yii - Malcolm Tang , Siong Yii (2014)

(untitled)
The presence of metallic single-walled carbon nanotubes (M-SWCNT) in as-prepared single-walled carbon nanotubes (SWCNT) poses a significant hurdle to integrate carbon nanotubes into semiconductor electronics. Here the findings of enriching semiconducting single-walled carbon nanotubes (S-SWCNT) using an aqueous two-phase system (ATPS) is reported. The solution containing as received SWCNT and polyethylene glycol (PEG), dextran, N-methylpyrrolidone (NMP) and water effectively separates into two distinct phases, with S-SWNT dominant in one phase while the M-SWCNT congregates in another phase. The separation process is due to the attraction of amine and S-SWCNT as reported by Chattopadhyay. Micro-Raman spectroscopy and Ultraviolet-Visible spectroscopy results show evidence of the removal of M-SWCNT in one of the phases especially for volume ratio 1:1 experiment. The ratio of M11/S22 in the top phase for VR 1.5 reaches 0.2574 compared to 0.1507 in the bottom phase. This finding presents ATPS as an easy, effective and low-cost purification method of carbon nanotubes.